Management and state regulation of the transport system of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2018)
Transport of Kazakhstan is a complex industry, carrying out its activities in cooperation with all sectorsof the country’s economy. Management of different types of transport is carried out within severalministries and departments, which implies close coordination and ensuring methodological unity in approachesto the development strategy. Transport is an important component in the economy of any state.The article deals with the management and state regulation of the transport system of the Republicof Kazakhstan. State regulation of transport logistics is carried out by the authorized state body – theTransport Committee under the Ministry of Investment and Development of the Republic of Kazakhstan.The activities of the transport system in Kazakhstan is regulated in accordance with laws, government programs, regulations, rules for the transport of passengers and luggage by road and other regulatorylegal acts. The results of the state regulation of the Transport Committee under the Ministry of Investmentand Development of the Republic of Kazakhstan can be characterized by its control and supervisory activitiesof railway transport. The author considers the main directions and tasks of the State Program forthe Development and Integration of the Transport System Infrastructure up to 2020, as well as the mainactions of state regulation of the transport system. Within the framework of international cooperation theRepublic of Kazakhstan signed a number of Agreements, Memorandums on international road transportof passengers and cargo.